Role of burnout on job level, job satisfaction, and task performance. Issue 5 (3rd July 2017) - Kim, Won Ho; Ra, Young-An; Park, Jong Gyu; Kwon, Bora
Abstract : Purpose: The purpose of this paper is to examine the mediating role of burnout (i.e. exhaustion, cynicism, professional inefficacy) in the relationship between job level and job satisfaction as well as between job level and task performance. Design/methodology/approach: The final sample included 342 Korean workers from selected companies. The authors employed the Hayes (2013) PROCESS tool for analyzing the data. Findings: The results showed that all three subscales of burnout (i.e. exhaustion, cynicism, professional inefficacy) mediate the relationship between job level and job satisfaction. However, only two mediators (i.e. cynicism, professional inefficacy) indicated the mediating effects on the association between job level and task performance. Originality/value: This research presented the role of burnout on the relationships between job level, job satisfaction, and task performance especially in South Korean organizational context. In addition to role of burnout, findings should prove helpful in improving job satisfaction and task performance. The authors provide implications and limitations of the findings.